Construction of a three-dimensional urothelium on-chip with barrier function based on urinary flow microenvironment. (1st July 2023) - Hou, Changhao; Gu, Yubo; Yuan, Wei; Zhang, Wukai; Xiu, Xianjie; Lin, Jiahao; Gao, Yue; Liu, Peichuan; Chen, Xiang; Song, Lujie
Abstract: The urothelium covers the inner surface of the urinary tract, forming a urinary tract barrier. Impairment of the integrity and dysfunction of the urinary tract barrier is associated with the occurrence and development of various diseases. The development of a three-dimensional model of the urothelium is critical for pathophysiological studies of this site, especially under physiological fluid shear stress stimulated by the urinary flow. In this study, a urothelium on-chip is fabricated with micromilling and replica molding techniques, which contains a microfluidic chip for cell culture and a pump-based fluid perfusion system. The mechanical properties of the human urinary tract are simulated by adjusting the concentration and degree of amino substitution of the gelatin methacrylate hydrogel. The matrix stiffness is similar to the natural urinary tract. Pulsatile flow and periodic flow are provided to simulate the fluid environment of the upper and lower urinary tracts, respectively. The results show that the physiological fluid shear stress could promote the differentiation and maturation of urothelial cells. The model could simulate the three-dimensional structure of urothelium and urinary flow microenvironment, showing morphological structure close to the natural urothelium, specific differentiation and maturation markers (uroplakin 2, cytokeratin 20), and urothelial barrier function.